β-Naphthol in Glycerol: A Versatile Pair for Efficient and Convenient Synthesis of Aminonaphthols, Naphtho-1,3-oxazines, and Benzoxanthenes - Ganesan, Subramaniapillai Selva; Rajendran, Narendran; Sundarakumar, Sankahr Ilathur; Ganesan, Asaithampi; Pemiah, Brindha (Synthesis, 2013)
Three-component Betti reaction was carried out in the environmentally benign, inexpensive, non-toxic solvent glycerol. Even in the absence of a catalyst, the reaction went completion with an unprecedented high rate and the expected Betti bases were obtained in up to 91% yield. The reaction works well for representative cyclic, acyclic, aliphatic, and aromatic amines and aldehydes. A benzoxanthene was also prepared in 93% yield following the same methodology with 20 mol% methanesulfonic acid catalyst.
Keywords: glycerol; Betti reaction; one-pot synthesis; naphtho-1,3-oxazine; benzoxanthenes